Should Patients With COVID-19 Receive Post-Discharge Thromboprophylaxis? Short Answers to Frequently Asked Questions - Pop Călin; Pop Marcel (Sciendo, 2022)
Infection with SARS-CoV-2 virus (COVID-19 disease) is associated with increased levels of inflammation and hypercoagulability. The risk of thrombosis includes the venous thromboembolic events (VTE), both distal venous thrombosis (DVT) and acute pulmonary embolism (PE) during a hospital stay that is ongoing after discharge, although how long this persists is unknown. The most frequent initial and late thrombotic complication is PE, as part of VTE. The evidence we have suggests quite a similar incidence (≤2%) of post-discharge VTE to that seen in other acutely ill patients. The current guidelines advise against extended thromboprophylaxis for patients who do not have suspected or confirmed VTE or other indications for anticoagulation. However, the guidelines recommend a careful individual risk-benefit assessment of VTE and bleeding probability, to determine whether an individual patient may merit ongoing prophylactic anticoagulation. A score such as IMPROVE DD can help identify those with potential benefit. Low-dose direct oral anticoagulants (DOACs) and low molecular weight heparins (LMVHs) were predominantly used, but the optimal duration (at least 14 days and up to 42 days) and the type of extended thromboprophylaxis is still under discussion. Future studies are therefore needed to clarify the VTE and bleeding outcomes in COVID-19 patients after hospital discharge.